2010
DOI: 10.1111/j.1939-1676.2009.0468.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Profiles and Clonal Relatedness of Canine and FelineEscherichia coliPathogens Expressing Multidrug Resistance in the United States

Abstract: Background: Antimicrobial resistance is increasing among Escherichia coli isolates associated with spontaneous infection in dogs and cats.Objectives: To describe E. coli resistance phenotypes and clonal relatedness and their regional prevalence. Animals: Isolates of E. coli (n 5 376) collected from dogs and cats in the United States between May and September 2005. Methods: Isolates submitted from the South, West, Northeast, and Midwest regions of the United States were prospectively studied. Phenotype was base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 32 publications
6
21
1
Order By: Relevance
“…However, as with previous investigations, this study confirmed that ENR resistance is highly associated with MDR isolates (with OR = 1.4; Tables 3 and S2; Karlowsky et al, 2006). In a previous publication, the study demonstrated that only 3% of the 84 E. coli isolates expressing single drug resistance were resistant to ENR, compared with 85% expressing SDR against b-lactams (Shaheen et al, 2010). Too, 50% of the isolates had an MIC of 0.03 or more and the MIC 90 of ENR is above the S-MIC BP .…”
Section: Discussionsupporting
confidence: 92%
“…However, as with previous investigations, this study confirmed that ENR resistance is highly associated with MDR isolates (with OR = 1.4; Tables 3 and S2; Karlowsky et al, 2006). In a previous publication, the study demonstrated that only 3% of the 84 E. coli isolates expressing single drug resistance were resistant to ENR, compared with 85% expressing SDR against b-lactams (Shaheen et al, 2010). Too, 50% of the isolates had an MIC of 0.03 or more and the MIC 90 of ENR is above the S-MIC BP .…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of anti-microbial-resistant E. coli observed in this study is comparable to previous studies of dogs in Canada, which have reported the prevalence of anti-microbial resistance to range from 0 to 20% (Murphy et al, 2009(Murphy et al, , 2010Leonard et al, 2012). There have also been similar studies of anti-microbial resistance in dogs conducted in Europe, the United States and Japan, with varying prevalences of anti-microbial resistance, ranging from 0 to 76% (Normand et al, 2000;De Graef et al, 2004;Costa et al, 2008;Shaheen et al, 2010;Harada et al, 2011). The variability in reported prevalence among these studies may be due to difference in study locations because different countries may have different patterns of using anti-microbials among companion animals, and there may be different levels of anti-microbial resistance in the community (Guardabassi et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…A similarly low ESC resistance in E. coli from dogs in Sweden was reported during 2010 – 2012 in SVARM, where approximately 1% of E. coli from UTIs in dogs had reduced susceptibility to cefotaxime (MIC > 1 mg/L) [33]. Higher prevalence of ESC resistant E. coli from various infections sites in dogs has been reported from other countries [4,34,37] and transmissible genes coding ESC resistance known to be common in isolates from humans have been found in bacteria isolated from pet animals [4,38,39]. In the present study, the only transmissible gene demonstrated was bla CMY2 , which in a contemporary study was found in only a small proportion of ESC resistant E. coli from humans in Sweden [33].…”
Section: Discussionmentioning
confidence: 61%